Indonesian Response to Covid-19 Poster as Indicator of Collective Visual Literacy (Bandung Case Study) - Maulina, Rini (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The covid-19 pandemic ongoing to this day in Indonesia, health protocol regulations established by the government to prevent transmission in the community. Various information of health protocols made by print and digital media is widely spread. However, it seems that does not have much impact, this can be seen from the increasing covid-19 transmission rate in Indonesia. It is necessary to see how the preferences of Indonesians, especially the people of Bandung who are teenagers in reading visual posters covid-19, the level of visual reading ability as a message is smeared with the level of visual literacy. The research was conducted through three poster themed covid-19 resulting from the application of visual argument methods wich is listed on questionnaire questions to measure the visual literacy capabilities of respondents. The analysis showed respondents aged between 18-24 years were more likely to choose posters with large portions of text, other results showed if the text was removed from the visual (visual argument method without text), the respondent could not capture the message on the poster. This has an impact on understanding the captured messages. This condition shows low levels of visual literacy among teenagers in Bandung.